The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1186/s13075-015-0763-6
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human SIRT1 protects against nutrient deprivation-induced mitochondrial apoptosis through autophagy induction in human intervertebral disc nucleus pulposus cells

Abstract: IntroductionNutrient deprivation is a likely contributor to intervertebral disc (IVD) degeneration. Silent mating type information regulator 2 homolog 1 (SIRT1) protects cells against limited nutrition by modulation of apoptosis and autophagy. However, little evidence exists regarding the extent to which SIRT1 affects IVD cells. Therefore, we conducted an in vitro study using human IVD nucleus pulposus (NP) cells.MethodsThirty-two IVD specimens were obtained from patients who underwent surgical intervention an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 42 publications
10
58
0
Order By: Relevance
“…Serum and nutrient deprivation decreased rabbit disc AF cell proliferation and metabolic activity and increased autophagy, apoptosis, and senescence . Serum deprivation‐induced autophagy in disc cells is consistent with prior reports . Our findings support the understanding of disc cell fate and the monitoring of autophagic flux.…”
Section: Serum and Nutrient Deprivation In Rabbit Disc Cellssupporting
confidence: 91%
“…Serum and nutrient deprivation decreased rabbit disc AF cell proliferation and metabolic activity and increased autophagy, apoptosis, and senescence . Serum deprivation‐induced autophagy in disc cells is consistent with prior reports . Our findings support the understanding of disc cell fate and the monitoring of autophagic flux.…”
Section: Serum and Nutrient Deprivation In Rabbit Disc Cellssupporting
confidence: 91%
“…A more recent study showed that resveratrol, prevented cell apoptosis by enhancing LC3-II/I and Beclin-1 protein levels, eventually leading to augmented macroautophagy in human NP cells of the IVD [42••]. This study was supported by another report by Miyazaki and colleagues, showing that exogenous administration of rhSIRT1 under low nutrient conditions, promoted autophagy, and prevented apoptosis of human NP-cultured cells [43]. Resveratrol-activated SIRT1, resulted in deacetylated p65/RelA, and attenuated iNOS expression following IL1β-mediated inflammatory stimulation of chondrocytes [44••].…”
Section: Sirt1 Survival Effectsupporting
confidence: 72%
“…Ito et al demonstrated that resident disc cells utilize autophagy to cope with harsh, low-nutrient environments [49]. Miyazaki et al showed that SIRT1, as a potent treatment agent for human degenerative IVD disease, can protect against nutrient deprivation-induced mitochondrial apoptosis through autophagy induction in human NP cells [50]. In our study, we also confirmed that ER stress can induce autophagy in human cultured NP cells.…”
Section: Discussionsupporting
confidence: 78%